2015
DOI: 10.4236/jbm.2015.36001
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Biodiversity Concerns in Eucalyptus Plantations Located in South China

Abstract: China's growing economy and changes in policies that encourage afforestation, particularly in the industrial sector, have led vast areas in south China to be planted with eucalyptus. These large areas of eucalyptus plantings have elicited environmental concerns for two primary reasons. First there is a concern related to the water demand of eucalyptus, in which it is feared these large areas of eucalyptus will deplete aquifers and create shortages in water supplies. The second concern is in regard to the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Regionally, a recent study highlights the importance of establishing mixed‐species plantations for diversity conservation and improvement of ecosystem functioning in subtropical China (Yang et al, ). However, several studies have reported decreasing biodiversity with increases in plantation area in tropical and subtropical China (Williams, ; Zhai et al, ). Thus, enhancing biodiversity in forest plantations should be of high priority in forest management, particularly in southeastern China.…”
Section: Introductionmentioning
confidence: 99%
“…Regionally, a recent study highlights the importance of establishing mixed‐species plantations for diversity conservation and improvement of ecosystem functioning in subtropical China (Yang et al, ). However, several studies have reported decreasing biodiversity with increases in plantation area in tropical and subtropical China (Williams, ; Zhai et al, ). Thus, enhancing biodiversity in forest plantations should be of high priority in forest management, particularly in southeastern China.…”
Section: Introductionmentioning
confidence: 99%
“…The HPNP is a protected area, however there are other plantations around this area. Therefore, it is important to encourage the surrounding plantations to improve resources by practicing environmental friendly performances, such as to develop mixed plantings of Eucalyptus with other native fast-growing species (Williams, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This could be accomplished by interplanting with indigenous tree species such as Betula alnoides, Schima superba, Michelia macclurei, and Castanopsis fissa (Sun, Huang, Yang, Schaefer, & Chen, 2017;Williams, 2015). This could be accomplished by interplanting with indigenous tree species such as Betula alnoides, Schima superba, Michelia macclurei, and Castanopsis fissa (Sun, Huang, Yang, Schaefer, & Chen, 2017;Williams, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the Eucalyptus plantations are intensively managed in a successive short-rotation regime (SSR), with a typical rotation length of 5-7 years (Li et al, 2015). This regime involves intensive forest management activities, including clear-cutting, whole-tree harvesting, prescribed burning, mechanical site preparation, fertilization, and herbicide application (Booth, 2013;Wen, Ye, Chen, Liu, & Liang, 2010;Williams, 2015;Zhou et al, 2018). This intensive management leads to serious disturbances on understory vegetation and soil, and in turn, has resulted in sharp declines in wood productivity (Tiarks & Haywood, 1996) and serious ecological problems, such as considerable degradation of soil quality (Zhang et al, 2015), decreases of understory plant species diversity (Wen et al, 2010; and high risk of exotic plant invasion (Jin et al, 2015;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%